The existential trilemma of EMU in a model of fiscal target zone - Pompeo Della Posta; Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
The lesson of the sovereign debt crises of the 2010s, and of the outbreak of the COVID-19 pandemic is that EMU irreversibility, if not to remain a wishful statement in the founding treaties, necessitates to be completed by carefully designed ramparts for extraordinary times beside regulations for ordinary times. In this paper we wish to contribute to this line of thought in two points. First, we highlight that when exposed to large, systemic shocks the EMU faces a trilemma: its integrity can only be saved by relaxing either monetary orthodoxy, or fiscal orthodoxy, or both. We elaborate this concept by means of a fiscal target zone model, where EMU member governments are willing to abide with the commitment to debt stability under the no-bailout clause only up to an upper bound of their feasible fiscal effort. Second, we show that EMU completion means providing a monetary and/or fiscal emergency backstop to the irreversibility principle. Drawing on the target-zone literature, we show how these devices can be designed in a consistent manner that minimises their extension and mitigates the moral hazard concerns. The alternative to these devices is not retaining both the EMU irreversibility and the twin orthodoxies, but reformulating the treaties with explicit and regulated exit procedures.
Keywords: E65; F34; F36; 330; COVID-19 pandemic; Fiscal Target Zone; Public Debt; Speculative Attacks; Fiscal Orthodoxy; Monetary Orthodoxy